Devils Hole Calcite Was Precipitated at ±1°C Stable Aquifer Temperatures During the Last Half Million Years. Issue 11 (10th June 2021) - Bajnai, David; Coplen, Tyler B.; Methner, Katharina; Löffler, Niklas; Krsnik, Emilija; Fiebig, Jens
Abstract: Subaqueous carbonates from the Devils Hole caves (southwestern USA) provide a continuous Holocene to Pleistocene North American paleoclimate record. The accuracy of this record relies on two assumptions: That carbonates precipitated close to isotope equilibrium and that groundwater temperature did not change significantly in the last 570 thousand years. Here, we investigate these assumptions using dual clumped isotope thermometry. This method relies on simultaneous analyses of carbonate ∆ 47 and ∆ 48 values and provides information on the existence and extent of kinetic isotope fractionation. Our results confirm the hypothesis that calcite precipitation occurred close to oxygen and clumped isotope equilibrium during the last half million years in Devils Hole. In addition, we provide evidence that aquifer temperatures varied by less than ±1°C during this interval. Thus, the Devils Hole calcite δ 18 O time series exclusively represents changes in groundwater δ 18 O values. Plain Language Summary: The oxygen isotope composition of cave carbonates records changes in Earth's climate. However, the reliability of such records depends on how stable the carbonate precipitation environment was. Here, we use a novel method called dual clumped isotope thermometry that can provide simultaneous information on a carbonate's growth temperature and whether any additional fractionation processes affected its oxygen and clumped isotope signatures. Specifically, we investigated the Devils Hole caves, which provide a reference oxygen isotope time series for North America. We find that groundwater temperature did not change significantly in the last half‐million years. Variations in the oxygen isotope composition of the deposited carbonates solely reflect variations in the oxygen isotope composition of the groundwater. Key Points: We use dual clumped isotope thermometry ( ∆ 47 and ∆ 48 ) to test for changes in calcite δ 18 O unrelated to variations in δ 18 O of groundwater Calcite δ 18 O record represents changes solely in δ 18 O of groundwater without contributions from variations in temperature and kinetics It is possible to achieve a stable carbonate precipitation environment over long timescales